The abundance of needs and the role of creativity in human evolution in a commodity economy - Lam, Nguyen Mai; Quoc, Nguyen Anh (Edelweiss Applied Science and Technology, 2025)
The content of this research aims to clarify the abilities and needs created to become the driving force for each individual to develop their capacity, contributing to the evolution of "Humanity" in developing a commodity economy. The article's content uses the methodology of human philosophy, social philosophy, and qualitative methods, especially the inversion method, to point out the transformation of different aspects of life in developing a commodity economy to achieve this goal. The result is that the system of human relations with nature becomes human communication, which is the process of creating society; performing natural functions becomes a task in the division of labor, and each individual becomes a mission, carrying different messages of life so that they are all equally good, with no discrimination against people. The conclusion of the article affirms: first, human life is the natural communication of "humanity"; it is the process of humans constantly creating life, while simultaneously producing tools to help "mechanize the body"; second, creativity is the value of socialized life, and each individual can develop their full potential in social communication; third, the coercion of mutual life in "human" society with products makes money the dominant force, and people become commodities; fourth, money is the subject that governs life in the commodity economy, so the life of money is free.